Adsorption mechanism of quaternary ammonium corrosion inhibitor on carbon steel surface using ToF-SIMS and XPS. (1st April 2023) - Wang, Luntao; Wang, Huiru; Seyeux, Antoine; Zanna, Sandrine; Pailleret, Alain; Nesic, Srdjan; Marcus, Philippe
Abstract: ToF-SIMS and XPS are combined to study the adsorption of tetradecyl-benzyldimethyl-ammonium (BDA-C14) bromide corrosion inhibitor on carbon steel surface. BDA-C14 forms a protective layer with N-containing polar head group interacting with carbon steel surface. The adsorbed inhibitor surface coverage strongly depends on immersion time and inhibitor concentration. A maximum and uniform coverage is found for sufficiently long exposure times at a critical inhibitor concentration of about 25 ppmw . The uniform adsorbed inhibitor layer formed on the surface mitigates the formation of iron chloride/hydroxide intermediates and thus enhances the corrosion protection of carbon steel in aggressive environment. Highlights: The adsorption of BDA-C14 corrosion inhibitor on carbon steel surface was studied by ToF-SIMS and XPS. The inhibitor forms a protective layer with N-containing polar head group interacting with carbon steel surface. The adsorbed inhibitor surface coverage strongly depends on immersion time and inhibitor concentration. The critical concentration for a maximum and uniformed inhibitor coverage on carbon steel is determined. The uniform adsorbed inhibitor layer on carbon steel can mitigate the formation of iron chloride/hydroxide intermediates.